Nanoproteomics Methods and Protocols - Toms, Steven A.; Weil, Robert J. (Methods in Molecular Biology, Methods and Protocols, 2011)
As two relatively new fields of study, proteomics and nanotechnology have developed in parallel with each other to allow an increased precision in the identification of post-translational protein modifications as well as to provide a more automated isolation and detection of rare proteins in both serum and tissues.  The Nanoproteomics: Methods and Protocols volume organizes and collects technical advances from leaders in the field to make laboratory protocols more readily available and understandable to those who are attempting to incorporate nanotechnologic techniques into their proteomic research. Conveniently divided into five sections, this detailed volume covers preliminary sample preparation, nanoscale fluidic devices and methods, nanostructured surfaces and nanomaterials, and nanoproteomic techniques to detect and understand protein and proteomic alterations specific to human pathology. Written in the highly successful series entitled Methods in Molecular Biology™, these chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step laboratory protocols that are readily reproducible, and tips on troubleshooting and avoiding known pitfalls.   Convenient and authoritative, Nanoproteomics: Methods and Protocols offers key procedures that are culled from the laboratories of leaders in the field of nanoproteomics with the aim of helping researchers in their standardization and proliferation of protocols that will lead to a more wide scale adoption and smoother progress in this vital field